Paradigma Maritim dalam Membangun Indonesia: Belajar dari Sejarah - Singgih Tri Sulistiyono (Universitas Gadjah Mada, 2016)
This article discusses the importance of the maritime paradigm in Indonesian national development. The maritime paradigm or what was once called as the maritime concept (wawasan bahari) or archipelagic concept (wawasan nusantara) is a development concept based on Indonesian identity as a maritime nation. The reinterpretation of this maritime paradigm is important in the context of the present period. First, to develop a clear conceptual and legal basis to the idea of the maritime state. Second, to implement in a practical manner the idea of the maritime state in the economic, political, social and cultural developments. By revitalizing and reinterpreting the maritime paradigm that is in line with the national identity it is hoped that national development based on the maritime state framework could achieve an optimal result.